Asynchronous l1 control for 2D switched positive systems with parametric uncertainties and impulses. (August 2020) - Wang, Jinling; Liang, Jinling; Qiu, Jianlong
Abstract: In this paper, the issue of asynchronous l 1 control is discussed for a class of two-dimensional (2D) switched positive systems with polytopic uncertain parameters and impulses. By choosing a suitable co-positive Lyapunov function and utilizing the mode-dependent average dwell time technique, sufficient conditions can be derived under which the closed-loop system induced by a set of asynchronous state feedback controllers is positive, exponentially stable and has l 1 disturbance attenuation performance. In addition, the design schemes for the asynchronously switched controllers are also provided in detail. Finally, two examples are provided to demonstrate the accuracy and tractability of the approach outlined in this paper.